How orthodox protestant parents decide on the vaccination of their children: a qualitative study - Ruijs Wilhelmina L M; Hautvast Jeannine L A; van IJzendoorn Giovanna; van Ansem Wilke J C; van der Velden Koos; Hulscher Marlies EJL (BMC, 2012)
Abstract Background Despite high vaccination coverage, there have recently been epidemics of vaccine preventable diseases in the Netherlands, largely confined to an orthodox protestant minority with religious objections to vaccination. The orthodox protestant minority consists of various denominations with either low, intermediate or high vaccination coverage. All orthodox protestant denominations leave the final decision to vaccinate or not up to their individual members. Methods To gain insight into how orthodox protestant parents decide on vaccination, what arguments they use, and the consequences of their decisions, we conducted an in-depth interview study of both vaccinating and non-vaccinating orthodox protestant parents selected via purposeful sampling. The interviews were thematically coded by two analysts using the software program Atlas.ti. The initial coding results were reviewed, discussed, and refined by the analysts until consensus was reached. Emerging concepts were assessed for consistency using the constant comparative method from grounded theory. Results After 27 interviews, data saturation was reached. Based on characteristics of the decision-making process (tradition vs. deliberation) and outcome (vaccinate or not), 4 subgroups of parents could be distinguished: traditionally non-vaccinating parents, deliberately non-vaccinating parents, deliberately vaccinating parents, and traditionally vaccinating parents. Except for the traditionally vaccinating parents, all used predominantly religious arguments to justify their vaccination decisions. Also with the exception of the traditionally vaccinating parents, all reported facing fears that they had made the wrong decision. This fear was most tangible among the deliberately vaccinating parents who thought they might be punished immediately by God for vaccinating their children and interpreted any side effects as a sign to stop vaccinating. Conclusions Policy makers and health care professionals should stimulate orthodox protestant parents to make a deliberate vaccination choice but also realize that a deliberate choice does not necessarily mean a choice to vaccinate.